Profitabilitas, Leverage, Dan Struktur Modal: Apakah Berdampak Terhadap Nilai PerusahaanProfitabilitas, Leverage, Dan Struktur Modal: Apakah Berdampak Terhadap Nilai Perusahaan - Setyani, Renny; Herawati, Ratna; Kustya Ulfa, Adilla; Resha Fatmawati, Elia (Universitas Dian Nuswantoro, 2024)
This study was conducted with the aim of analyzing the impact of profitability (ROE), leverage (DAR), and capital structure (DER) on firm value (PBV) in energy sector companies for the 2019-2022 period. The data used in this study are secondary data in the form of financial reports obtained from the official website of the Indonesia Stock Exchange (IDX). The sample of this study used purposive sampling method and obtained data as many as 28 energy companies that met the predetermined criteria. The analysis method in this study uses regression analysis method. The results of the data analysis conducted show that profitability impacts firm value, while leverage and capital structure have no impact on firm value.